Correlation at two-dimensional charge-transfer FeSe interface. Issue 84 (3rd October 2019) - Huang, Yulong; Hu, Yong; Hu, Feng; Yang, Ruizhe; Li, Changning; Armstrong, Jason N.; Ren, Shenqiang
Abstract : The 2D FeSe hybrid interface exhibits charge transfer triggered strongly correlated phenomena under light illumination. Abstract : The charge transfer and spin coupling effects are explored at the interface of two-dimensional (2D) superconducting FeSe nanosheets and molecular photochromic potassium-7, 7, 8, 8-tetracyanoquinodimethane (KTCNQ). Light-induced conductivity in 2D FeSe nanosheets is enhanced by the electron doping from KTCNQ by the destabilized spin-Peierls phase through their interface. Furthermore, the spin coupling at the interface of FeSe and KTCNQ shifts the dimerization transition temperature of KTCNQ. Our results suggest 2D exfoliated FeSe nanosheets as a versatile strongly correlated platform for the study of interfacial electron doping and spin coupling.